Confirmation of initial antiphospholipid antibody positivity depends on the antiphospholipid antibody profile. Issue 8 (14th August 2013) - Pengo, V.; Ruffatti, A.; Del Ross, T.; Tonello, M.; Cuffaro, S.; Hoxha, A.; Banzato, A.; Bison, E.; Denas, G.; Bracco, A.; Padayattil Jose, S.
Summary: Background: The revised classification criteria for the antiphospholipid syndrome state that antiphospholipid (aPL) antibodies (lupus anticoagulant [LAC] and/or anticardiolipin [aCL] and/or anti‐β2 ‐glycoprotein I [aβ2 GPI] antibodies) should be detected on two or more occasions at least 12 weeks apart. Consequently, classification of patient risk and adequacy of treatment may be deferred by 3 months. Objectives: In order to early classify patient risk, we evaluated whether aPL positivity confirmation is related to aPL antibody profiles. Patients and Methods: Consecutive patients referred to our center who were initially positive in one or more tests exploring the presence of aPL were tested after 3 months. During a 4‐year period, 225 patients were initially positive in one or more tests, and 161 were available for confirmation after 3 months. Patients were classified as triple‐positive ( n = 54: LAC +, aCL +, aβ2 GPI +, same isotype), double‐positive ( n = 50: LAC –, aCL +, aβ2 GPI +, same isotype) and single‐positive ( n = 53: LAC or aCL or aβ2 GPI antibodies as the sole positive test). Results: Among subjects with triple positivity at initial testing, 98% (53 of 54) had their aPL profile confirmed after 12 weeks. The double‐positive and single‐positive groups had data confirmed in 42 of 50 (84%) and 23 of 57 (40%) subjects, respectively. Conclusions: Our results show that high‐risk subjects with triple‐positive aPL profiles are identified early, at the time of the initial screening tests.